Climate Change and the Risk of Malaria Transmission in Iran. Issue 1 (20th August 2019) - Hanafi-Bojd, Ahmad Ali; Vatandoost, Hassan; Yaghoobi-Ershadi, Mohammad Reza
Abstract: Climate change is an important factor affecting the dynamics of the vectors population and, hence, the risk of vector-borne diseases. This study aimed to predict the environmental suitability for malaria vectors in Iran under climate change scenarios in 2030s and 2050s. Literature search was performed to find documents on the spatial distribution of Anopheles stephensi Liston, 1901, Anopheles culicifacies s.l. Giles, 1901, Anopheles fluviatilis s.l. James, 1902, Anopheles superpictus s.l. Grassi, 1899, Anopheles dthali Patton, 1905, Anopheles maculipennis s.l. Meigen, 1818, and Anopheles sacharovi Favre, 1903 (Diptera: Culicidae) published between 1970 and 2017. The bioclimatic data under three climate change scenarios (representative concentration pathway 2.6 [RCP2.6], RCP4.5, and RCP8.5) and MaxEnt model were used to predict the ecological niches for each species. Comparison between the two study periods under the three scenarios for each species revealed that RCP8.5 would reduce the area at risk for An. culicifacies s.l., An. dthali and An. superpictus s.l. in the 2050s compared to the 2030s, but the reverse will be induced by RCP2.6 and RCP4.5 scenarios. For An. fluviatilis s.l., RCP2.6 will reduce the risk areas in the 2050s, whereas an increase is expected under the two other scenarios. Moreover, all scenarios would decrease the high-risk areas of An. maculipennis s.l. in the 2050s. For An. sacharovi, RCP2.6 would increase its high-risk areas, whereas RCP4.5 and RCP8.5 would decrease its exposure. The high-risk area of An. stephensi is expected to increase under RCP8.5 in the 2030s and RCP4.5 in 2050s, but it will be almost unchanged or reduced under other scenarios.